A smart surface with switchable wettability by an ionic liquid. Issue 18 (28th February 2017) - Chang, Li; Liu, Hongliang; Ding, Yi; Zhang, Jiajing; Li, Li; Zhang, Xiqi; Liu, Mingzhu; Jiang, Lei
Abstract : A temperature-responsive surface exhibiting switchable wettability between ILphilicity and ILphobicity by an ionic liquid has been developed. Abstract : Smart control of surface wettability by ionic liquids (ILs) is significant for designing IL-related intelligent materials and devices. Herein, we present mixed molecular brushes comprised of poly(phenylethyl methacrylate) and 1 H, 1 H, 2 H, 2 H -perfluorodecyltrimethoxysilane (PPhEtMA- co -PFDMS) grafted surfaces that are capable of dynamically regulating 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([EMIm][NTf2 ]) wettability. 1 H NMR and quartz crystal microbalance characterization demonstrate that the wettability changes result from a temperature-dominated cation–π interaction between [EMIm][NTf2 ] and PPhEtMA- co -PFDMS brushes.